You need to remember that you may write the factored form of a polynomial when you know its roots, hence you need to find the roots of quadratic `x^2 + 8x - 12 = 0` .
You should use the quadratic formula such that:
`x_(1,2) = (-b+-sqrt(b^2 - 4ac))/(2a)`
The coefficients a,b,c occur in the standard form of quadratic `ax^2 + bx + c = 0` .
Comparing the given quadratic to the standard form yields a=1, b=8, c=-12.
You need to substitute 1 for a, 8 for b and -12 for c in the quadratic formula such that:
`x_(1,2) = (-8+-sqrt(64 + 48))/2`
`x_(1,2) = (-8+-sqrt112)/2`
`` `x_(1,2) = (-8+-4sqrt7)/2 =gt x_(1,2) = (-4+-2sqrt7)`
Hence, evaluating the roots of quadratic you may write the factored form of quadratic such that: `x^2 + 8x - 12 = (x+ 4 - 2sqrt7)(x + 4+ 2sqrt7) = (x+4)^2 - 28` .